Comparison of sequential cryoprobe and biopsy forceps in endobronchial ultrasound-guided transbronchial needle aspiration for mediastinal and hilar lesions: a prospective observational study - Ching-Kai Lin; Sheng-Yuan Ruan; Hung-Jen Fan; Hao-Chun Chang; Yen-Ting Lin; Chao-Chi Ho (Annals of Medicine)
Background Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a safe and widely used technique for diagnosing mediastinal/hilar lesions. Recent studies showed that combining EBUS-TBNA with cryobiopsy (EBUS-transbronchial mediastinal cryobiopsy, EBUS-TMC) or forceps biopsy (EBUS-intranodal forceps biopsy, EBUS-IFB) enhances diagnostic accuracy by obtaining larger tissue samples. However, limited data is comparing the efficacy of EBUS-TMC and EBUS-IFB. This study aims to assess the effectiveness of these biopsy techniques in diagnosing mediastinal and hilar lesions.Methods Patients with mediastinal/hilar lesions who underwent EBUS-TBNA and mediastinal biopsy from November 2022 to March 2024 were enrolled. Following needle aspiration, cryobiopsy and forceps biopsies were performed. The primary endpoint was diagnostic accuracy.Results A total of 219 mediastinal/hilar lesions were evaluated in 183 patients. EBUS-TMC demonstrated higher diagnostic accuracy than EBUS-IFB (95.4% vs. 84.9%, p < 0.001). Subgroup analysis also showed superior yield rates for EBUS-TMC (96.1% vs. 89.6%, p = 0.027 in all malignancies; 96.1% vs. 86.8%, p = 0.042 in malignancies for re-biopsy; 95.2% vs. 76.2%, p = 0.040 in non-lung cancer malignancies; 93.8% vs. 73.8%, p = 0.002 in benign processes). The tissue specimens obtained via EBUS-TMC were significantly larger than those via EBUS-IFB (16.3 mm2 vs. 3.1 mm2, p < 0.001). Adding EBUS-IFB did not improve accuracy when EBUS-TMC was already used with EBUS-TBNA. No severe complications leading to death or disability were observed.Conclusions EBUS-TMC is an effective diagnostic and auxiliary method for mediastinal/hilar lesions, enhancing yield rates and tissue acquisition.